1995
DOI: 10.1002/jso.2930580208
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic study of patients with Borrmann type iv gastric carcinoma

Abstract: Between 1979 and 1993, 665 Japanese patients with advanced gastric cancer underwent surgery at our hospital. These patients were divided into two groups, consisting of 102 patients with Borrmann type IV carcinoma, and the remaining 563 patients with all other types of gastric carcinoma, which were then compared clinicopathologically. In the patients with Borrmann type IV carcinoma, 77.4% of the lesions demonstrated poorly differentiated adenocarcinoma, and 99 patients were classified as Stage III or IV. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 15 publications
7
47
0
2
Order By: Relevance
“…In most of these works, such variables were analyzed in groups of patients undergoing any type of gastric resection, without distinguishing curative from palliative approaches 3,5,7,9,[14][15][16][17][18][19] , while a smaller number detained on the study of these factors solely in the curative operation 8,11,20 , similar to our series. Like our study, several others confirmed that the B IV was associated with known factors of poor [5][6][7]11,14,16 . Diagnosis in advanced stages, poorly differentiated histology, serosal invasion and high incidence of lymph node involvement are factors that directly influence the prognosis, causing lower rates of curative operations, which can vary between 31 and 52% 3,[5][6][7][8]20 and are in agreement with our data, which was 42.3% (52/123).…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In most of these works, such variables were analyzed in groups of patients undergoing any type of gastric resection, without distinguishing curative from palliative approaches 3,5,7,9,[14][15][16][17][18][19] , while a smaller number detained on the study of these factors solely in the curative operation 8,11,20 , similar to our series. Like our study, several others confirmed that the B IV was associated with known factors of poor [5][6][7]11,14,16 . Diagnosis in advanced stages, poorly differentiated histology, serosal invasion and high incidence of lymph node involvement are factors that directly influence the prognosis, causing lower rates of curative operations, which can vary between 31 and 52% 3,[5][6][7][8]20 and are in agreement with our data, which was 42.3% (52/123).…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
“…In 1858, Brinton coined the term linitis plastica 4 to describe the infiltrative gastric carcinoma occupying the entire stomach (diffuse form), also called cirrous carcinoma in English literature 3 . Approximately 10 to 15% of all gastric adenocarcinomas are classified as type B IV, and some studies show its association with factors known to be of poor prognosis [5][6][7] . Thus, despite advances in treatment of gastric cancer, the surgical results of the B IV remains poor, with lower rates of curative resection [5][6][7][8] and survival 6,7,9 in comparison with other types of gastric carcinomas.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…SGC has been shown to possess unique clinicopathological characteristics and a poor survival outcome despite curative gastrectomy (10)(11)(12)(13)(14)(15)(16)(20)(21)(22)(23). One reason for the poor prognosis specific to SGC is the difficulty in early detection.…”
Section: A B C Discussionmentioning
confidence: 99%
“…By contrast, numerous studies have commented on the definition (1-4), incidence (10), significance (11), pathology (12), prognosis (10)(11)(12) and management strategy (13)(14)(15)(16) of SGC pertaining solely to the early and the final phase of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Scirrhous carcinoma of the stomach is a poorly di erentiated adenocarcinoma typically characterized by growing vast ®brous stroma, and in®ltrative and rapid expansion (Sugimachi, 1993). It should be mentioned that the prognosis of scirrhous carcinoma is still poor, despite recent advances in the treatment of gastric carcinoma (Kitamura et al, 1995). Several peptide growth factors including epidermal growth factor (EGF) may be involved in its development and/or malignant progression.…”
Section: Introductionmentioning
confidence: 99%